Odpowiedzi

2010-03-28T18:49:30+02:00
A) 9-3x + 2x = 8 - 2x - 2
9 - 5x = 6 - 2x
9 - 6 = 2x + 5x
3 = 7x\3
x = 2.33
b) 4 - 15 - 5x = 3x - 2x
-11 - 5x = x
-11 = x + 5x
-11 = 6x\razy - 11
x = -66
c) 4x + 15 x + 30 = 4 + 2x - 4
19x + 30 = 1 + 2x
30 - 1 = 2x - 19x
29 = -17x\razy 29
x = -493
d) 7x - 2x = 2x - 2 + 1
5x = -1 - 2x
2x - 5x = -1
-3x = -1\razy - 3
x = 3

Najlepsza Odpowiedź!
2010-03-28T18:57:06+02:00
A)3(3-X)+2x=8-2(x-1)
9-3x+2x=8-2x+2
-3x+2x+2x=-9+8+2
x=1
Spr:
3(3-1)+2*1=8-2(1-1)
6+2=8-2*0
8=8

b)4-5(3-X)=-X-(3-2x)
4-15+5x=-x-3+2x
5x+x-2x=-4+15-3
4x=8|:4
x=2
Spr:
4-5(3-2)=-2-(3-2*2)
4-5=-2+1
-1=-1

C)4x+5-(3x+6)=2(2+x)-4
4x+5-3x-6=4+2x-4
4x-3x-2x=-5+6+4-4
-x=1|*(-1)
x=-1
Spr:
4*(-1)+5-[3*(-1)+6]=2[2+(-1)-4
-4+5-(-3+6)=2-4
-4+5+3-6=2-4
-2=-2

D)x-(7+2x)=2(x-1)+1
x-7-2x=2x-2+1
x-2x-2x=7-2+1
-3x=6|:(-3)
x=-2
Spr
-2-[7+2*(-2)]=2[-2-1]+1
-2-[7-4]=-6+1
-2-3=-5
-5=-5
2010-03-28T19:04:01+02:00
A)3(3-X)+2x=8-2(x-1)
9-3x+2x-8+2x-2=0
x= 1
spr. 3(3-1) + 2*1= 8-2(1-1)
6+2= 8
8=8
L=P
b)4-5(3-X)=-X-(3-2x)
4-15+5x= -x-3+2x
4x= 8//4
x=2
spr. 4-5(3-2)= -2-(3-2*2)
4-5= -2+1
-1=-1
L=P
C)4x+5-(3x+6)=2(2+x)-4
4x+5-3x-6= 4+2x-4
-x= 1//(-1)
x= -1
spr.4*(-1)+5-(3*(-1)+6)=2(2+(-1))-4
-4+5-3=2-4
-2=-2
L=P
D)x-(7+2x)=2(x-1)+1
x-7-2x= 2x-2+1
-3x=6//(-3)
x= -2
spr. -2-(7+2*(-2))=2((-2)-1)+1
-2-3=-6+1
-5=-5
L=P

6-19= 10+1